2021
DOI: 10.1111/1759-7714.13954
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of lung cancer with hemophagocytic lymphohistiocytosis caused by immune checkpoint inhibitors

Abstract: We report the cases of two patients with secondary hemophagocytic lymphohistiocytosis caused by immune checkpoint inhibitors, who were diagnosed using the recently developed HScore. The first patient presented with fever, cytopenia, and elevated liver enzyme levels at 46 days post‐pembrolizumab administration. The HScore was 175. The second patient developed an immune‐related adverse event at 30 days after the final pembrolizumab dose. The HScore was 185. Hemophagocytic lymphohistiocytosis was confirmed in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Both patients experienced fever on day 7 and splenomegaly on day 10. A transient fever was also reported in other cases in existing literature (19,20). The concept of an immune-related fever that occurred 2-10 days after the infusion of ICIs, put forward by Michot et al (21), may explain this phenomenon.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Both patients experienced fever on day 7 and splenomegaly on day 10. A transient fever was also reported in other cases in existing literature (19,20). The concept of an immune-related fever that occurred 2-10 days after the infusion of ICIs, put forward by Michot et al (21), may explain this phenomenon.…”
Section: Discussionmentioning
confidence: 68%
“…The fever and splenomegaly may be signs of enhanced immune activation. Previous research has shown that diseases that present prior to the diagnosis of HLH, such as thyroiditis, appendicitis, edema, and flareup of preexisting ADs, may be the expression of immune overactivation (19,(22)(23)(24). Moreover, markedly elevated interleukin (IL)-6 was detected in both patients, which could be a possible treatment target for HLH.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, there are no published reports of cytotoxic chemotherapy-induced combined AIHA and HLH; there is only one such reported case that was caused by programmed death 1 blockade. 2 In addition, AIHA 3 and HLH 4 have been separately reported as irAEs of ICIs. Therefore, the hematologic irAEs that were observed in the present case were likely to be attributed to atezolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…HLH as an irAE is lethal; 23% of patients with this irAE die, even if they receive treatment. 4 In addition, HLH can worsen rapidly. Therefore, early diagnosis and treatment are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…HLH is divided into primary (genetic) and secondary (acquired) [ 86 ], with the latter being triggered by viral infections (EBV, Dengue virus, HIV virus, CMV, hepatitis A), bacteria ( Rikettsia spp., tuberculosis), parasites and fungi ( Histoplasma spp., Leishmania spp., Plasmodium spp., Toxoplasma, P. jiroveci, Aspergillus spp. ), autoimmune disorders such as systemic lupus erythematosus and adult-onset Still disease, solid tumors, and drugs [ 86 , 88 ].…”
Section: Methodsmentioning
confidence: 99%